Comparison of drug-eluting balloon versus drug-eluting stent treatment of drug-eluting stent in-stent restenosis: A meta-analysis of available evidence. (1st September 2016) - Bajraktari, Gani; Jashari, Haki; Ibrahimi, Pranvera; Alfonso, Fernando; Jashari, Fisnik; Ndrepepa, Gjin; Elezi, Shpend; Henein, Michael Y.
Abstract: Background: In-stent restenosis (ISR) remains an important concern despite the recent advances in the drug-eluting stent (DES) technology. The introduction of drug-eluting balloons (DEB) offers a good solution to such problem. Objectives: We performed a meta-analysis to assess the clinical efficiency and safety of DEB compared with DES in patients with DES-ISR. Methods: A systematic search was conducted and all randomized and observational studies which compared DEB with DES in patients with DES-ISR were included. The primary outcome measure—major adverse cardiovascular events (MACE)—as well as individual events as target lesion revascularization (TLR), stent thrombosis (ST), myocardial infarction (MI), cardiac death (CD) and all-cause mortality, were analyzed. Results: Three randomized and 4 observational studies were included with a total of 2052 patients. MACE (relative risk [RR] = 1.00, 95% confidence interval (CI) 0.68 to 1.46, P = 0.99), TLR (RR = 1.15 [CI 0.79 to 1.68], P = 0.44), ST (RR = 0.37[0.10 to 1.34], P = 0.13), MI (RR = 0.97 [0.49 to 1.91], P = 0.93) and CD (RR = 0.73 [0.22 to 2.45], P = 0.61) were not different between patients treated with DEB and with DES. However, all-cause mortality was lower in patients treated with DEB (RR = 0.45 [0.23 to 0.87, P = 0.019) and in particular when compared to only first generation DES (RR 0.33 [0.15–0.74], P = 0.007). There was no statistical evidence for publication bias. Conclusions: The results of this meta-analysis showed that DEB and DES have similar efficacy and safety for the treatment of DES-ISR.